Evaluación del epicarpio de cacao Theobroma cacao en combinación con p.e.t (polietileno tereftalato) en módulos de aglomerado por medio de una resina como ligante para uso industrial - Verdezoto Marín, Diego Armando (2016)
This project of investigation centres on the evaluation of the epicarpio of cocoa on union with the P.E.T., in the production of a prototype of agglomerate, the aim is to evaluate the combination of the percentage of the epicarpio close to the P.E.T., as to determine the quantity of suitable resin and to establish a time of ideal pressing. The raw material was obtained in what concerns the epicarpio of cocoa, in the canton Quevedo Provincia of Los Ríos and P.E.T's small leaves., in the canton El Empalme Province of the Guayas. For the production of the modules of agglomerate, the raw material was selected, then I dry her to the environment for three days to be crushed, dose and prepare the raw material of agreement for him to the proposed combinations, the process of stuck was according to the treatments, I homogenize the mixture locating them in permanent molds, compacting them in a time determined in a pressing in cold. The mathematical model that I use was a design of blocks with arrangement factorial AxBxC, being the Factor To; Percentage of epicarpio of Theobroma cocoa with p.e.t. in three levels with two repetitions; ao (70 %-30 %), a1 (50 % - 50 %), a2 (80 % - 20 %), Factor B; Time of pressing bo (6min, b1 (8min) and the Factor C; Resin c0 (blancola), c1 (duracol), since three factors of studies exist applies an ADEVA to itself with a level of significancia of 0.5 %. The evaluation of results realized by means of the statistical package STATGRAPHICS centurion the XVIth version 16.1.18, and for the difference determination of the averages between the treatments and the levels and there used TUKEY's test (p <0.05). To determine that levels are the most ideal in the treatments the following variables were analyzed: flexion, traction, pull screw, elasticity and dampness respectively every treatments with his repetition. One concluded that in what concerns the Factor To (percentage of epicarpio and p.e.t.), 70 %-30 %, Factor B (Time of pressing) in the period of 6min is the fact that he presents major efficiency, and in the Factor C: quantity of resin.70 % - 30 % recommend to him to use the relation, in what it corresponds to the percentage of epicarpio of cocoa and of P.E.T, in the pressing to use the time of 6 min, and finally the employment of both resins.